Prehospital triage for endovascular clot removal in acute stroke patients. Issue 1 (4th August 2016) - Suzuki, Yu; Hasegawa, Yasuhiro; Tsumura, Kohtaro; Ueda, Toshihiro; Suzuki, Kazunari; Sugiyama, Makoto; Nozaki, Hiroyuki; Kawaguchi, Shojiro; Nakane, Makoto; Nagashima, Goro; Kitamura, Takayuki; Yokomine, Kengo; et al.
Abstract : Aim: To establish prehospital triage in accordance with the new guidelines for endovascular therapy, we retrospectively analyzed the monitoring data of the city‐wide transportation system using the Maria Prehospital Stroke Scale (MPSS), a novel prehospital stroke scale for emergency medical technicians (EMTs) to predict the likelihood of thrombolytic therapy after transportation. Methods: Kawasaki City, Japan, has six comprehensive stroke centers (CSCs) and six primary stroke centers (PSCs). In CSCs, endovascular therapy can be carried out 24 h a day, 7 days a week, but not in PSCs. There is no "drip and ship" protocol for further endovascular therapy from PSCs to CSCs. We determined the predictive value of MPSS scoring by the EMTs for the performance of endovascular therapy after transportation. Results: There were 2031 patients (mean age, 71.1 ± 13.3 years) registered from April 2012 to March 2015. Multivariate logistic regression analysis indicated that the MPSS score and type of stroke center were independent predictors for performance of endovascular therapy. In particular, the odds ratio (OR) for endovascular therapy was significant for MPSS score 3 (OR, 2.914; 95% confidence interval (CI), 1.152–7.372; P = 0.024), MPSS score 4 (OR, 5.474; 95%CI, 2.300–13.029; P = 0.000), and MPSS score 5 (OR, 11.459; 95%CI, 4.334–30.296; P = 0.000) when MPSS score 1 was set as a reference. The diagnostic accuracy of the MPSS score evaluated by EMTs was 0.689 (95%CI, 0.627–0.751). Conclusions: Prehospital triage using MPSS scores evaluated by EMTs can predict the likelihood of performance of endovascular therapy after transportation, and may become a tool offering a flexible solution for designing a new transportation protocol.